2022
DOI: 10.1039/d2tc00208f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in Pr3+-activated persistent phosphors

Abstract: Lanthanide-doped phosphors with persistent luminescence have attracted much interest owing to their unique “self-luminescing” feature and broad application potentials. Among all lanthanide ions, Pr3+ exhibits versatile persistent luminescence in a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 165 publications
0
16
0
Order By: Relevance
“…, the 4f5d level is energetically below the 1 S 0 level and sufficiently spaced from the nearest 3 P 2 level.) and a very small Stokes shift (less than 3000 cm −1 ), 35,37 as shown in Fig. 2a.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…, the 4f5d level is energetically below the 1 S 0 level and sufficiently spaced from the nearest 3 P 2 level.) and a very small Stokes shift (less than 3000 cm −1 ), 35,37 as shown in Fig. 2a.…”
Section: Resultsmentioning
confidence: 75%
“…The parity-allowed 4f5d → 4f 2 inter-configurational transition of Pr 3+ enables Pr 3+ -doped solids to be promising candidates for efficient UVC luminescence. 35–37 Inspired by this, UVC luminescence of Pr 3+ has been reported in a series of inorganic solids in the past few decades, with the representative ones including fluorides ( e.g. , LiYF 4 :Pr 3+ ), aluminates ( e.g.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…To the best of our knowledge, the only work with an overview of known UV PersL materials is back in 2019, with discussion covering only ≈15 UV PersL materials and more focus on the UV PersL performance of Pb 2+ , Ce 3+ , Bi 3+ , and Pr 3+ doped materials. [21,20] However, due to the recent growing interest in UV PersL materials, the number has burgeoned to ≈60, and more types of hosts and emitters are used to achieve excellent UV PersL since then. Furthermore, new potentials (such as "solarblind" tagging and therapeutics) have been discussed compared to the Vis and IR counterparts in the past couple of years.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of extensive research in recent years, a few deep-UV-emitting persistent phosphors activated by Pr 3+ have been reported. 22–27 For example, Yang et al reported a Cs 2 NaYF 6 :Pr 3+ UVC phosphor, which showed persistent UVC emission for ∼2 h in the dark after high-energy X-ray irradiation. 22 To take it forward, the Pan group developed a series of Pr 3+ -doped silicate UVC persistent phosphors and reported that a 254 nm UV lamp can give a self-sustained UVC output for more than 12 h in the dark.…”
Section: Introductionmentioning
confidence: 99%